Histological Characterization and Histochemical Profiling of the Heart of Prenatal Goat (Capra hircus) - Gayatri, Raj; Taluja, J. S.; Vaish, Rakhi; Singh, Nripendra; Lade, Diksha; Tekam, Shashi; Bharti, Shashi; Jadav, Kajal Kumar (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during July to October, 2020 at the Department of Veterinary Anatomy, College of Veterinary Science and Animal Husbandry, Nanaji Deshmukh Veterinary Science University, Jabalpur, Madhya Pradesh, India to investigate the histological and histochemical features of the hearts of 18 prenatal healthy goats (Capra hircus). The heart shape varied among the groups; groups I and II exhibited an ovoid shape, while group III had a flattened cone shape. Histological examinations revealed both superficial and deep cardiac muscle fibers in the atrial walls, forming muscular arches in the atrium. The ventricular myocardium was composed of three distinct layers of muscle fibers, with the middle layer being the thickest. The left ventricular wall was significantly thicker than the right. The cardiac valves were identified as endocardial flaps. Histochemical analysis showed that collagen and elastic fibers were more abundant in the atria than in the ventricles, with collagen primarily surrounding blood vessels. Reticular fibers formed networks in both the atria and ventricles. A weak to moderate periodic acid-Schiff (PAS) reaction was observed in the atria, ventricles, blood vessels, and atrioventricular cusps. Metachromasia was noted in both the atria and ventricles. Additionally, DNA content in atrial nuclei exhibited moderate staining across all age groups. These findings provide a detailed histological and histochemical description of prenatal goat heart development, contributing to the understanding of fetal cardiovascular maturation.